2020
DOI: 10.1177/0333102420958384
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of localized and widespread pressure pain hypersensitivity in patients with tension-type headache: A systematic review and meta-analysis

Abstract: Objective This meta-analysis evaluates pressure pain sensitivity values in symptomatic and distant pain-free areas comparing individuals with tension-type headache to controls. Databases and data treatment Electronic databases were searched for cross-sectional or prospective case-control studies comparing pressure pain thresholds in patients with tension-type headache to headache-free controls. Data were extracted by three reviewers. The methodological quality was assessed by the Newcastle-Ottawa Quality Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…The presence of widespread sensitivity to pressure pain is a clinical manifestation of central sensitization in CTTH. In fact, a recent meta-analysis concluded that sensitivity to pressure pain seems to be widespread in CTTH and confined to the head and cervical spine in FETTH [38], supporting those findings identified by the current SC analysis.…”
Section: Discussionsupporting
confidence: 87%
“…The presence of widespread sensitivity to pressure pain is a clinical manifestation of central sensitization in CTTH. In fact, a recent meta-analysis concluded that sensitivity to pressure pain seems to be widespread in CTTH and confined to the head and cervical spine in FETTH [38], supporting those findings identified by the current SC analysis.…”
Section: Discussionsupporting
confidence: 87%
“…There is evidence supporting the presence of an altered nociceptive processing in patients with TMDs expressed by widespread lower pain thresholds to mechanical but not thermal stimuli [ 12 ]. In fact, widespread pressure hypersensitivity seems to be a common feature of musculoskeletal pain conditions of the head-neck region, such as TMD [ 12 ], or tension-type headaches [ 13 ].…”
Section: Clinical Examination Temporomandibular Pain Disordersmentioning
confidence: 99%
“…Pressure pain threshold (PPT) is a static measure of pain reflecting the basal state of pain perception in relation to the pressure experienced a patient [ 85 ]. In fact, PPT is one of the quantitative sensory tests most commonly used for characterization of TTH [ 5 ] and migraine [ 4 ]. Nevertheless, its reliability and validity are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, migraine has been ranked the third-highest cause of disability worldwide in both genders under the age of 50 years [ 3 ]. Both headaches feature the presence of pressure pain hyperalgesia [ 4 , 5 ]. This assumption is based on the results from several studies investigating sensitivity to pressure pain in both TTH [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ] and migraine [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation